1999
DOI: 10.2307/2991640
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive Failure Rates: New Estimates from the 1995 National Survey of Family Growth

Abstract: Levels of contraceptive failure vary widely by method, as well as by personal and background characteristics. Income's strong influence on contraceptive failure suggests that access barriers and the general disadvantage associated with poverty seriously impede effective contraceptive practice in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
120
0
7

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(131 citation statements)
references
References 10 publications
4
120
0
7
Order By: Relevance
“…However, imperfect use contributes to failure rates as high as 30% [1]. Effective OCP use requires method commitment (i.e., considering one's birth control method to be OCP) as well as OCP use consistent with the method's pharmacology and mechanism of action (i.e., method adherence).…”
Section: Introductionmentioning
confidence: 99%
“…However, imperfect use contributes to failure rates as high as 30% [1]. Effective OCP use requires method commitment (i.e., considering one's birth control method to be OCP) as well as OCP use consistent with the method's pharmacology and mechanism of action (i.e., method adherence).…”
Section: Introductionmentioning
confidence: 99%
“…The National Survey of Family Growth estimates that 9% of women using oral contraceptive pills will have an unintended pregnancy within the first year, as compared with only 0.001%, 0.14%, and 0.7% of women who use the subdermal implant, levonorgestrel IUD, or copper IUD, respectively. 8 However, these data were derived from retrospective surveys that asked women to recall their contraceptive use and pregnancies over the past (on average) 3.75 years. 4,8 The failure rate for DMPA injections in our study is lower than other reported rates because we categorized a pregnancy as a contraceptive failure only in users who had returned for injections; thus, these rates represent "perfect use" rather than typical use, given that more than 40% of women who use DMPA will discontinue use in the first year.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, these data were derived from retrospective surveys that asked women to recall their contraceptive use and pregnancies over the past (on average) 3.75 years. 4,8 The failure rate for DMPA injections in our study is lower than other reported rates because we categorized a pregnancy as a contraceptive failure only in users who had returned for injections; thus, these rates represent "perfect use" rather than typical use, given that more than 40% of women who use DMPA will discontinue use in the first year. 10 Half of all pregnancies in the United States are unintended, and half of those result from con- Bars depict the cumulative percentage of participants who had a contraceptive failure with long-acting reversible contraception (LARC), depot medroxyprogesterone acetate (DMPA), or pill, patch, or ring (PPR) at 1, 2, or 3 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although condoms are essential to prevent sexually transmitted diseases, the efficacy and effectiveness depends on the correct use and the possible occurrence of physical complications such as breakage and slippage. Thus, it is not surprising that some reports reveal estimations showing that pregnancy rate may be as high as 14% in the first year [195] during condom use. There are several other methods that can be used by men to avoid pregnancy, but there is an urgent need for an effective reversible male contraceptive.…”
Section: Future Perspectivesmentioning
confidence: 99%